Music therapy in modulating immune responses and enhancing cancer treatment outcomes - Fu, Ye; Wu, Ke; Zhuang, Jiajia; Chen, Yisheng; Jia, Lina; Luo, Zhiwen; Sun, Rong (Frontiers in Immunology, 2025)
Music therapy, an intersection of art and science, is gaining recognition as a complementary approach in cancer care. This review systematically explores its mechanisms, applications, and effectiveness, with a focus on its impact on the tumor microenvironment (TME), particularly immune signaling and inflammation at single-cell resolution. Evidence shows that music therapy alleviates psychological symptoms—such as anxiety and depression—and physical discomforts including pain, fatigue, and nausea. Beyond symptomatic relief, it also modulates immune responses, especially in immune cell populations that influence tumor-associated inflammation and cancer progression. Advances in single-cell technologies may begin to explain how music therapy modulates immune signaling pathways within the TME, potentially enhancing treatment efficacy.Despite its non-invasive, cost-effective nature and high patient acceptability, music therapy remains underutilized in oncology. Further large-scale studies are needed to elucidate its molecular mechanisms, refine intervention models, and validate its role in immune modulation. As research advances, music therapy holds promise as a valuable component of integrative oncology, supporting patient recovery and immune homeostasis.